On construction of real-time monitoring system for sport cruiser motorcycles using NB-IoT and multi-sensors - Kristiani, E.; Yu, T.-H.; Yang, C.-T. (Sensors, 2024)
This study leverages IoT technology to develop a real-time monitoring system for large motorcycles. We collaborated with professional mechanics to define the required data types and system architecture, ensuring practicality and efficiency. The system integrates the NB-IoT for efficient remote data transmission and uses MQTT for optimized messaging. It also includes advanced database management and intuitive data visualization for enhancing the user experience. For hardware installation, the system follows strict guidelines to avoid damaging the motorcycle`s original structure, comply with Taiwan`s legal standards, and prevent unauthorized modifications. The implementation of this real-time monitoring system is anticipated to significantly reduce safety risks associated with mechanical failures as it continuously monitors inappropriate driving behaviors and detects mechanical abnormalities in real time. The study indicates that the integration of advanced technologies, such as the NB-IoT and multi-sensor systems, can lead to improved driving safety and operational efficiency. Furthermore, the research suggests that the system`s ability to provide instant notifications and alerts through the platforms` instant messaging can enhance user responsiveness to potential hazards, thereby contributing to a safer riding experience.